Analysis of Measurement Results on AMR to Determine P2TL Operation Targets at PT PLN (Persero) UP3 Indramayu - Agus Siswanto; Rendy Chandra Nova; Mudofar Baehaqi (Mestro, 2021)
The Kwh Meter Automatic Meter Reading (Kwh Meter AMR) system is a system for recording electricity meters that is carried out automatically and remotely. Data communication sent by the AMR kWH meter at PT PLN (Persero) UP3 Indramayu uses an AMR modem as an electronic kWH meter interfacing with a wireless telecommunications network. The AMR kWh meter has a feature that besides recording the use of electrical energy used, it also records voltage, electric current, power factor, and the recording time of the customer's electricity usage meter is faster. PT PLN (Persero) UP3 Indramayu can carry out distribution network management which makes it easier in terms of distributing energy to customers and monitoring the use of electrical energy by customers. In operating the kWh meter AMR system can reduce losses caused by abnormal use of electrical energy by customers. These abnormalities include incorrect Wiring, errors in wiring on the Kwh Meter, Unbalance Current, unbalanced electricity usage by customers, Blank Kwh and AMR modem hangs/damages so that the communication signal is unstable and fails to retrieve data on electricity consumption by customers. To overcome these abnormalities, a check is carried out on the customer according to the findings of abnormal deviations in the AMR application. The use of unmeasured electrical energy during the Kwh Blank abnormality is 4,619 kWh with a total follow-up billing fee of Rp. 6,936,537.-. The results of the abnormality category of Incorrect Wiring were carried out by normalizing wiring errors in the Kwh Meter phase S and Phase T. The results of the Unbalance Current abnormality category, the electricity consumption at the customer at that time was not balanced, that is, the T phase was not used by the customer. The results of the AMR Modem abnormality category are replaced by the AMR Modem so that the customer's electricity consumption is again disabled in the AMR application.